Effects of lipid-based nutrient supplements and infant and young child feeding counseling with or without improved water, sanitation, and hygiene (WASH) on anemia and micronutrient status: results from 2 cluster-randomized trials in Kenya and Bangladesh. Issue 1 (9th January 2019) - Stewart, Christine P; Dewey, Kathryn G; Lin, Audrie; Pickering, Amy J; Byrd, Kendra A; Jannat, Kaniz; Ali, Shahjahan; Rao, Gouthami; Dentz, Holly N; Kiprotich, Marion; Arnold, Charles D; Arnold, Benjamin F; et al.
ABSTRACT: Background: Anemia in young children is a global health problem. Risk factors include poor nutrient intake and poor water quality, sanitation, or hygiene. Objective: We evaluated the effects of water quality, sanitation, handwashing, and nutrition interventions on micronutrient status and anemia among children in rural Kenya and Bangladesh. Design: We nested substudies within 2 cluster-randomized controlled trials enrolling pregnant women and following their children for 2 y. These substudies included 4 groups: water, sanitation, and handwashing (WSH); nutrition (N), including lipid-based nutrient supplements (LNSs; ages 6–24 mo) and infant and young child feeding (IYCF) counseling; WSH+N; and control. Hemoglobin and micronutrient biomarkers were measured after 2 y of intervention and compared between groups using generalized linear models with robust SEs. Results: In Kenya, 699 children were assessed at a mean ± SD age of 22.1 ± 1.8 mo, and in Bangladesh 1470 participants were measured at a mean ± SD age of 28.0 ± 1.9 mo. The control group anemia prevalences were 48.8% in Kenya and 17.4% in Bangladesh. There was a lower prevalence of anemia in the 2 N intervention groups in both Kenya [N: 36.2%; prevalence ratio (PR): 0.74; 95% CI: 0.58, 0.94; WSH+N: 27.3%; PR: 0.56; 95% CI: 0.42, 0.75] and Bangladesh (N: 8.7%; PR: 0.50; 95% CI: 0.32, 0.78; WSH+N: 7.9%, PR: 0.46; 95% CI: 0.29, 0.73). In both trials, the 2 N groups also had significantly lower prevalences of iron deficiency, iron deficiency anemia, and low vitamin B-12 and, in Kenya, a lower prevalence of folate and vitamin A deficiencies. In Bangladesh, the WSH group had a lower prevalence of anemia (12.8%; PR: 0.74; 95% CI: 0.54, 1.00) than the control group, whereas in Kenya, the WSH+N group had a lower prevalence of anemia than did the N group (PR: 0.75; 95% CI: 0.53, 1.07), but this was not significant ( P = 0.102). Conclusions: IYCF counseling with LNSs reduced the risks of anemia, iron deficiency, and low vitamin B-12. Effects on folate and vitamin A varied between studies. Improvements in WSH also reduced the risk of anemia in Bangladesh but did not provide added benefit over the nutrition-specific intervention. These trials were registered at clinicaltrials.gov as NCT01590095 (Bangladesh) and NCT01704105 (Kenya).